ENGLISH READING SKILL STUDENT IN THE PERSPECTIVE OF THE NATIONAL LITERATURE COMMUNITY - Sofiana, Via Novia; Suryadi (Jurnal Ilmiah Pendidikan Citra Bakti, 2023)
Based on the results of this survey, determine the level of English reading proficiency of students in a national community. It was possible to conclude that students' reading and literacy skills improved through the use of quantitative descriptive techniques and questionnaires. A descriptive study is one that provides the most thorough picture or description of the situation while ignoring the behavior of the selected object. For informational purposes, reading is a sophisticated and challenging action or activity. Reading activities involve both internal and external factors. The ability to read is one of the most beneficial abilities one can have in both their academic and social lives. It comes before all other skills as well. The results of the respondents' favorite genre can be used to infer that a student in a Taksara literacy community increased their interest in literacy and reading by 16% to 25%, and their ability to read in English increased by 6.3% to 68.8%. One of them is the Taksara literacy community, whose goal is to encourage readers of all ages and equip the Indonesian generation to widen the doors of literacy for future generations. As a result, there are numerous literacy movements that are led by locals or other members of the community rather than by the government. One of them is the Taksara literacy community, whose goal is to support readers of all ages and enable the Indonesian generation to open literacy windows for all generations. The intellectual, pragmatic, and linguistic values of reading are connected to its cognitive attitude.